Critical Review of East Asia - South America Trade - Shintaro Hamanaka; Aiken Tafgar (Asian Development Bank (ADB), 2013)
There is a general consensus that trade between East Asia and South America is becoming increasingly important. However, we know little about the actual dynamic development of this inter-regional trade. This paper examines whether the trend of East Asia–South America trade is a general phenomena or a country- and commodity-specific issue, and whether the increase in trade values has a solid basis in terms of commodity diversification and/or price and quantity effects. While South America has an overall trade surplus with East Asia, detailed country and commodity analysis of inter-regional trade reveal several potential weaknesses in South America's trade with East Asia. Our research finds that (i) the increase in trade between the two regions can be explained mainly by the increase in the People's Republic of China's (PRC) trade with South America, (ii) the increase in the PRC's imports from South America is limited to a few commodities, (iii) the increase in East Asia's imports from South America is due partly to commodity price increases, and (iv) the PRC has started to export various types of electronics and machinery products to South America. Overall, East Asia's exports to South America seem to show more promising signs of growth than South America's exports to East Asia.
hdl:11540/2337
Keywords: F13; F14; F15; O24; 330; Regional integration/cooperation; trade policy; inter-regional trade; East Asia trade; South America trade; Regionale Wirtschaftsintegration; Internationale Wirtschaftsbeziehungen; Ostasien; Südamerika